EVALUASI MODUL PRAKTIKUM BERBASIS PROBLEM BASED LEARNING PADA ALAT PERAGA CONTINOUSLY VARIABLE TRANSMISSION (CVT) SEPEDA MOTOR - Monica Pratiwi; Sugeng Pramudibyo; Muhammad Yasser Arafat; Andi Maga Umara (Jambura Journal of Engineering Education, 2024)
This study aims to develop a practical module based on Problem Based Learning on a motorcycle Continuously Variable Transmission (CVT) teaching aid and to determine the feasibility of the developed motorcycle Continuously Variable Transmission (CVT) teaching aid module. The method used in this study is the RD (Research and Development) method and uses the 4D model (four-D model) consisting of the Define, Design, Develop, and Disseminate stages. The results of the study indicate that a practical module has been produced on a motorcycle Continuously Variable Transmission (CVT) teaching aid for the motorcycle technology course at the Mechanical Engineering Education Study Program, Faculty of Engineering, Gorontalo State University. The level of feasibility of the problem based learning practical module on the motorcycle Continuously Variable Transmission (CVT) teaching aid at the Mechanical Engineering Education Study Program, Faculty of Engineering, Gorontalo State University, is determined through validation of the practical module design, expert validation by material experts and media experts and student response tests with results meeting the criteria of "Very Good" and is suitable for use as teaching materials that support student learning.